Multi-Substrate Specificity and the Evolutionary Basis for Interdependence in tRNA Editing and Methylation Enzymes - Dixit, Sameer; Henderson, Jeremy C.; Alfonzo, Juan D. (Frontiers in Genetics, 2019)
Among tRNA modification enzymes there is a correlation between multi-substrate specificity and heteromultimerization. In general, enzymes that modify a conserved residue in tRNAs of different sequences tend to adopt a heterodimeric structure. Presumably, such changes in the oligomeric state of enzymes, to gain multisubstrate recognition, are driven by the need to accommodate and catalyze a particular reaction in different substrates while maintaining high specificity. This review focuses on two classes of enzymes where the case for multimerization as a way to diversify molecular recognition can be made. We will highlight several new themes with tRNA methyltransferases and will also discuss recent findings with tRNA editing deaminases. These topics will be discussed in the context of several mechanisms by which heterodimerization may have been achieved during evolution and how these mechanisms might impact modifications in different systems.